Cupcake Diaries : Emma, Smile and Say "Cupcake!" - Coco Simon (India Simon Spotlight, 2012)
The Special Day wedding salon is running an ad in the local newspaper, and they want Emma to model in the advertisement. When a local department store also wants to use Emma as a model, she$1 (Bs suddenly very much in demand! But after running all over New York City for auditions (and being told over and over she (3z(Bjust isn$1 (Bt right(3y(B) Emma realizes being a model is a lot tougher than she thought. Does Emma really want to be America$1 (Bs next top model, or is being a part of the Cupcake Club sweet enough?s
Keywords: Fantasy -- Fantasy